2020
DOI: 10.1002/adfm.202003273
|View full text |Cite
|
Sign up to set email alerts
|

Delamination‐Free Functional Graphene Surface by Multiscale, Conformal Wrinkling

Abstract: Obtaining a delamination-free wrinkled functional graphene surface in layered systems is an interesting challenge because the interface is usually too weak to withstand interfacial stress mismatch, which can trigger mechanical instability. In this paper, a general strategy is proposed toward addressing the delamination limitation imposed by fabricating conformal graphene wrinkles with bilayer systems of poly(methyl methacrylate) (PMMA) and polydimethylsiloxane (PDMS). To improve the interfacial strength, a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…It should be noted that dried BC–GO–PGA–CaFT films showed a wrinkled surface morphology (Figure j), while the surface morphology of dried BC–PGA–CaFT films was rather smooth (Figure c). The formation of this wrinkled structure in the GO-containing sample is likely due to the large surface area of GO flakes, which tend to become curly and aggregate and absorb on the surface of BC fibers. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that dried BC–GO–PGA–CaFT films showed a wrinkled surface morphology (Figure j), while the surface morphology of dried BC–PGA–CaFT films was rather smooth (Figure c). The formation of this wrinkled structure in the GO-containing sample is likely due to the large surface area of GO flakes, which tend to become curly and aggregate and absorb on the surface of BC fibers. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…The formation of this wrinkled structure in the GO-containing sample is likely due to the large surface area of GO flakes, which tend to become curly and aggregate and absorb on the surface of BC fibers. 41,42 Thermogravimetric analysis (TGA) curves (Figure S5) showed that the residual mass values of BC−GO−CaFT and BC−GO−PGA−CaFT lie between the ones of pure GO and BC−PGA−CaFT, confirming the presence of GO in the final composites. The GO content in the final composites can be calculated based on the residual mass ratio of TGA curves, 26 and the dried BC−GO−PGA films showed a 48.3% wt GO content.…”
Section: ■ Introductionmentioning
confidence: 89%
“…This attribute is highly promising in constructing stimuli-responsive material as well as realizing wireless and remote-control materials . However, one vital issue in graphene-based composites is the unsatisfactory inert bonding, low bending rigidity, and thus interfacial mechanical-mismatch with other flexible materials. These features make the fabrication of layered composites complex and challenging, and cause delamination or interfacial sliding at the interface among responsive layers under the shear stress. Although many efforts have been made in chemical or plasma modification of RGO sheets for enhancing interfacial bonding and flexibility, these approaches could inevitably induce harmful defects or deactivation of the responsive component(s) .…”
Section: Introductionmentioning
confidence: 99%
“…[21,55] Moreover, graphene with wrinkled surface provides attractive application prospects in the development of flexible functional devices and highly sensitive sensors. [13,56] The long-term goal of various transfer methods is to preserve the desirable characteristics of graphene, including high electron mobility, high transparency, and high impermeability, [57,58] etc. Undoubtedly, the development of the transfer methods will promote the research and applications of LAG films and GNs.…”
Section: Introductionmentioning
confidence: 99%